Eigenvalue problems for nonlinear elliptic equations with unilateral constraints - Filippakis, Michael
In this paper we study eigenvalue problems for hemivariational and variational inequalities driven by the p-Laplacian differential operator. Using topological methods (based on multivalued versions of the Leray–Schauder alternative principle) and variational methods (based on the nonsmooth critical point theory), we prove existence and multiplicity results for the eigenvalue problems that we examine.